Seroprevalence of fascioliasis in the eastern region of Turkey: an eight-year investigation - Beyhan, Yunus Emre; Yılmaz, Hasan (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Fascioliasis is a zoonotic disease and one of the most neglected infectious diseases in humans. Its prevalence has been increasing significantly during the last decades. This study aimed to investigate the prevalence of fascioliasis using direct microscopy and indirect hemagglutination (IHA) technique in a region in Eastern Anatolia of Turkey. Material and Methods: This study was conducted on the serum samples obtained from 817 patients (372 male and 445 female) between 2011 and 2018, who were suspected to have fascioliasis. IHA was used to investigate anti-Fasciola hepatica antibodies in the serum samples. Stool specimens were obtained from the seropositive patients and were examined with the native-Lugol method to identify the parasites. Results: It was determined that 5.5% (45/817) of all the patients were F. hepatica seropositive and 6.4% (52/817) were borderline positive. Positivity was 5.7% (21/372) among males and 5.4% (24/445) among females, and the difference in the infection rates between these groups was not significant (p=0.913). The highest number of patients who applied to the clinic was in the “45 and over” age group (317 patients); 270 patients were in the 25-44 age group. A maximum positivity of 10.3% was observed in the 7-14 age group. Conclusion: Previously, fascioliasis was considered a rare infection in humans; however, it has emerged as an important public health problem in the world. Considering fascioliasis in patients with clinical symptoms, not only with direct observation but also using serological methods, would be effective in early diagnosis and treatment of the disease.